(untitled) (Research, Society and Development, 2022)
Evaluation is a subcomponent of the control process, which, in turn, is the fourth step of the management process. Its essentiality lies in that it is through it that decisions are made about the effectiveness and efficiency of management processes. As science constantly advances in this field, it is necessary to periodically survey each management process step’s state of the art of each subcomponent. In this sense, this study aimed to take stock of what evaluation is and what are its operationalization steps. The method used was the scientific-technological one, characterized by elaborating guiding research questions, data collection on scientific bases, data organization, and generating the sought answers. The results showed that a) evaluation is the decision process that allows comparing what was planned with what was executed, b) the evaluation process is composed of five basic steps: planning, execution, monitoring, analysis of results, and reporting analytical, and c) each step has its criteria to be executed. The conclusion shows that changing the order of these steps can decisively compromise the intended objectives of the entire evaluation process, which is knowledge about the difference between what was planned and what was executed.